A Non-Contact Strain Measurement Method - Mohd Noramin bin Md Isa, Mohd Noramin (Universiti Teknologi Petronas, 2009)
Optical method is a non contact method for strain measurement. This project aims to investigate the use of simple tools to obtain strain values. The objective is to evaluate the suitability of strain measurement method by processing images captured using a digital camera. The tools include an 8 MP digital camera, a 5kN Universal Tensile Machine and Adobe Photoshop CS3 as the image processing software. A polyethylene specimen was loaded in tension according to ASTM D638 testing method while the digital camera captured the image of specimen being loaded. After that the images was processed using the Adobe Photoshop CS3 software. Strain was calculated using the change in length of lines of colored pixels on the specimen. The results showed good agreement between experimental and literature values. Mild steel, however, is not analyzed its profile because of incorrect mounting orientation of specimen. The findings suggest that optical method developed here in UTP has the potential to be a useful method for strain measurement. My recommendation is that the results of the strain values are verified using extensometer and image processing is automated using Matlab or Visual Basic.